Downsizing Organization: A Systematic Literature Review - Habibi, Fikri; Sumartono, Sumartono; Santoso Haryono, Bambang; Khairul Muluk, MR. (Journal of World Science, 2023)
Downsizing is the most popular strategic choice in organizational change, especially in the private sector. The strategy often chosen in downsizing is reducing employees, eliminating structure and function to produce efficiency, productivity, and competitiveness. However, a study is needed to elaborate on the concept of downsizing. The purpose of this research is to map the downsizing concept, describe how this strategy is implemented, its dynamics and development, as well as the effectiveness level of downsizing strategy. This research takes the form of a systematic literature review, which involves an assessment based on articles/publications related to downsizing. Downsizing articles are sourced from the Scopus database, and then mapped based on the number of articles per year, authors, countries, affiliations, and sponsors. As a result, the goal of downsizing has not been supported by strong evidence in the field because downsizing and efficiency do not have a strong correlation. Indeed, downsizing results in negative impacts on both organizations and employees. His mistake was to put the strategy of reducing employees and financial efficiency as the main goal. Therefore, downsizing must be part of a paradigmatic organizational change strategy and not merely serve as a short-term strategy.